Periapical healing outcome following non-surgical endodontic intervention among diabetic patients: A systematic review conducted according to PRISMA guidelines and the Cochrane handbook for systematic reviews of interventions - Butta Viswanath; Harsh Priyank; Sahana Shivakumar; Akshayraj Langaliya; Aravind D Kumbhar; Ashima Jakhar; Gabriele Cervino; Giuseppe Minervini (Elsevier, 2024)
Background: Periapical diseases are common dental conditions that require non-surgical endodontic intervention (NEI) for successful treatment. However, the impact of diabetes mellitus (DM) on the periapical healing (PH) outcome in diabetic patients remains somewhat unclear. This review aimed to evaluate the PH outcome following endodontic intervention among DM-afflicted individuals. Methods: A comprehensive search was conducted across multiple electronic databases to identify relevant studies. Specifically, a set of selection criteria was applied to select studies that assessed PH outcomes in individuals with DM who underwent different treatment protocols. Data extraction and quality assessment were performed following predetermined protocols. The risk of bias (RoB) 2 assessment tool evaluated the quality of the included studies. Results: A total of 11 studies met the inclusion criteria and were included in the investigation. Four studies showed a higher incidence of apical periodontitis in diabetic individuals compared to controls, and five studies reported reduced healing and success rates in this group. Overall, nine studies have shown that DM has a negative impact on periapical outcomes. This suggests that DM is an important factor in the prognosis of endodontic intervention. The assessment tools used were PAI, PR, SC, and FD analysis. RoB-2 assessed the included studies as having a moderate RoB. Conclusion: This review provides compelling evidence that DM patients experienced a noticeable negative impact on PH outcomes compared to the control population. These findings highlight the importance of considering the diabetic status of patients when assessing the prognosis of periapical diseases and planning interventions for NEI. Further research is needed to validate these results and explore potential mechanisms underlying the observed associations.